Power storage device and method of manufacturing the power storage device
Patent Information
- Application Number
- JP2023130165
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-09
Smart Images

Figure 2025025421000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electricity storage device in which a first terminal member is fixed to a case member constituting a case via a first resin member and a second terminal member is fixed to the case member via a second resin member, and to a manufacturing method for the electricity storage device. [Background technology]
[0002] As an electric storage device, a battery is known in which a positive electrode terminal member is fixed to a case member (specifically, a rectangular plate-shaped case lid member) constituting a rectangular box-shaped case via a first resin member and a negative electrode terminal member is fixed to the case member via a second resin member. Specifically, the positive electrode terminal member is inserted into a first insertion hole provided in the case lid member and extends from the inside to the outside of the case, and the first resin member is airtightly joined to the case lid member and the positive electrode terminal member while insulating them from each other, thereby fixing the positive electrode terminal member to the case lid member. The negative electrode terminal member is inserted into a second insertion hole provided in the case lid member and extends from the inside to the outside of the case, and the second resin member is airtightly joined to the case lid member and the negative electrode terminal member while insulating them from each other, thereby fixing the negative electrode terminal member to the case lid member.
[0003] In manufacturing such a battery, the first resin member and the second resin member may be insert-molded. That is, in a state where the positive electrode terminal member is inserted into the first insertion hole of the case lid member and the negative electrode terminal member is inserted into the second insertion hole of the case lid member, the first resin member and the second resin member are simultaneously insert-molded using a single resin material. Note that, for example, Patent Document 1 (see Figs. 2, 6, 7, etc.) is an example of a conventional technique for simultaneously insert-molding the first resin member and the second resin member using a single resin material. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2022-079172 Summary of the Invention [Problem to be solved by the invention]
[0005] However, it has been found that during the above-mentioned insert molding, cracks (fissures) may occur along the boundary due to cohesive failure in the first resin member near the boundary with the positive terminal member, and cracks (fissures) may occur along the boundary due to cohesive failure in the second resin member near the boundary with the negative terminal member. If such cracks occur during insert molding, they may extend further during actual use of the battery, causing the seal between the positive terminal member and the first resin member and the seal between the negative terminal member and the second resin member to break down.
[0006] In addition, the positive electrode terminal member made of aluminum and the negative electrode terminal member made of copper have different linear expansion coefficients, etc. Therefore, when the first resin member and the second resin member are molded using a single resin material, if the resin material used for insert molding is adjusted so that the above-mentioned cracks do not occur in the first resin member on the positive electrode side, the above-mentioned cracks are likely to occur in the second resin member on the negative electrode side. Conversely, it has been found that if the above-mentioned resin material is adjusted so that the above-mentioned cracks do not occur in the second resin member on the negative electrode side, the above-mentioned cracks are likely to occur in the first resin member on the positive electrode side.
[0007] The present invention has been made in consideration of the current situation, and provides an electricity storage device in which cracks are less likely to occur in the first resin member and the second resin member during insert molding, and which can maintain good sealing properties between the first terminal member made of aluminum and the first resin member, and between the second terminal member made of copper and the second resin member, and a method for manufacturing the electricity storage device. [Means for solving the problem]
[0008] (1) One aspect of the present invention for solving the above-mentioned problems is an electricity storage device including a case member having a first insertion hole and a second insertion hole, a first terminal member made of aluminum inserted into the first insertion hole of the case member, a second terminal member made of copper inserted into the second insertion hole of the case member, a first resin member inserted by insert molding that hermetically bonds the case member and the first terminal member while insulating them from each other and fixes the first terminal member to the case member, and a second resin member inserted by insert molding that hermetically bonds the case member and the second terminal member while insulating them from each other and fixes the second terminal member to the case member, wherein the first resin member has a resin linear expansion coefficient α of 1.6×10 -5 ~2.7×10 -5 Within the range of (1 / K) (1.6×10 -5 ≦α≦2.7×10 -5 ) and the second resin member is made of a second resin material different from the first resin material and having a resin material flexural modulus E of 17 GPa or less (E≦17).
[0009] As described above, conventionally, the first resin member and the second resin member were molded using a single resin material, and therefore it was not possible to achieve both a good seal between the first terminal member and the first resin member and a good seal between the second terminal member and the second resin member. In contrast, in the above-mentioned electricity storage device, the first resin member and the second resin member are molded using different resin materials. The first resin material constituting the first resin member has a resin linear expansion coefficient α of 1.6×10 -5 ~2.7×10 -5 (1 / K) range, and the second resin material constituting the second resin member has a resin material flexural modulus E of 17 GPa or less. This makes it difficult for cracks to occur in the first resin member and the second resin member during insert molding, and makes it possible to maintain good sealing properties between the first terminal member and the first resin member and between the second terminal member and the second resin member.
[0010] The reason for this is not necessarily clear at present. The present inventors have investigated the resin linear expansion coefficient α and the resin flexural modulus E of the resin material used in insert molding, and the sealing performance between the terminal member and the resin member (see Figs. 11 to 14). The details will be described later. As a result, in relation to the first terminal member made of aluminum, the magnitude of the resin bending elasticity modulus E of the first resin material does not significantly affect the sealing performance between the first terminal member and the first resin member (see FIG. 12). On the other hand, the magnitude of the resin linear expansion coefficient α of the first resin material significantly affects the sealing performance between the first terminal member and the first resin member (see FIG. 11), and it has been found that by setting the value of the resin linear expansion coefficient α within the aforementioned range, the sealing performance can be maintained favorably. In relation to the second terminal member made of copper, the magnitude of the resin linear expansion coefficient α of the second resin material does not significantly affect the sealing performance between the second terminal member and the second resin member (see Fig. 14). On the other hand, the magnitude of the resin flexural modulus E of the second resin material significantly affects the sealing performance between the second terminal member and the second resin member (see Fig. 13), and it has been found that by keeping the value of the resin flexural modulus E within the aforementioned range, the sealing performance can be maintained well.
[0011] The temperature range of the "resin linear expansion coefficient α" of the first resin material is −40 to 65° C. A specific method for measuring the resin linear expansion coefficient α will be described later. The "resin material flexural modulus E" of the second resin material is obtained by performing a three-point bending test using a test piece of the second resin material (length 10 mm x width 1.5 mm x thickness 1.5 mm). A specific method for measuring the resin material flexural modulus E will be described later.
[0012] The resin material flexural modulus E of the second resin material is preferably 10 GPa or more (10≦E≦17). If the resin material flexural modulus E is too small, the strength of the second resin member is likely to be significantly reduced, and the stress generated in the second resin member during insert molding may exceed the strength of the second resin member, causing a risk of cracks in the second resin member. Examples of the "electricity storage device" include secondary batteries such as lithium ion secondary batteries, sodium ion secondary batteries, and calcium ion secondary batteries, and capacitors such as lithium ion capacitors.
[0013] (2) The energy storage device described in (1) may be such that the first resin material includes a thermoplastic first main resin, a thermoplastic first elastomer, and a first filler, and the second resin material includes a thermoplastic second main resin, a thermoplastic second elastomer, and a second filler.
[0014] As described above, by making the first resin material a resin material having a first thermoplastic elastomer and a first filler in addition to a first thermoplastic main resin, the resin linear expansion coefficient α of the first resin material can be easily adjusted. Also, by making the second resin material a resin material having a second thermoplastic elastomer and a second filler in addition to a second thermoplastic main resin, the resin flexural modulus E of the second resin material can be easily adjusted.
[0015] The term "main resin" refers to the material that has the largest weight ratio among the materials that make up the resin material, excluding fillers. Examples of "thermoplastic main resins" include thermoplastic resins such as polyethylene (PE), polypropylene (PP), polybutylene (PB), polyphenylene sulfide (PPS), polytetrafluoroethylene (PTFE), and perfluoroalkoxyalkane (PFA). Examples of "thermoplastic elastomers" include thermoplastic polyurethane elastomers (TPU) obtained from diisocyanates such as 4,4'-diphenylmethane diisocyanate (MDI) and high molecular weight diols. Examples of high molecular weight diols include polyester diols (PES), polyether diols (PET), polycaprolactone diols (PCL), and polycarbonate diols (PCD).
[0016] Examples of the "filler" include glass fillers made of alkali glass, E glass, etc., alumina fillers made of alumina, potassium titanate fillers made of potassium titanate, etc. Examples of the shape of the "filler" include spherical, plate-like, fibrous, and needle-like shapes. The first resin material may include materials other than the above-mentioned first main resin, first elastomer, and first filler, and the second resin material may include materials other than the above-mentioned second main resin, second elastomer, and second filler.
[0017] (3) In the energy storage device according to (1) or (2), it is preferable that the first terminal seal portion to which the first resin member is hermetically joined of the first terminal member has a surface on which stand first nanopillars having a height of 50 nm or more, the first nanopillars being made of aluminum particles having a diameter of 100 nm or less joined in a string of beads, and the first resin member is hermetically joined to the first terminal seal portion with the first resin material filled between the standing first nanopillars, and the second terminal seal portion to which the second resin member is hermetically joined of the second terminal member has a surface on which stand second nanopillars having a height of 50 nm or more, the second nanopillars being made of copper particles having a diameter of 100 nm or less joined in a string of beads, and the second resin member is hermetically joined to the second terminal seal portion with the second resin material filled between the standing second nanopillars,
[0018] In the above-mentioned power storage device, the above-mentioned first nanopillars stand in a row on the surface of the first terminal seal part of the first terminal member, and the first resin material is filled between these first nanopillars to hermetically bond the first resin member to the first terminal seal part. This increases the bonding strength between the first terminal seal part of the first terminal member and the first resin member, and makes it possible to maintain particularly good sealing performance between the first terminal member and the first resin member. Furthermore, the above-mentioned second nanopillars stand in a forest on the surface of the second terminal seal part of the second terminal member, and the spaces between these second nanopillars are filled with the second resin material, so that the second resin material is hermetically bonded to the second terminal seal part. This increases the bonding strength between the second terminal seal part of the second terminal member and the second resin member, and makes it possible to maintain particularly good sealing performance between the second terminal member and the second resin member.
[0019] Examples of the "particles containing aluminum" constituting the first nanopillar include particles made of aluminum, particles made of aluminum oxide, particles made of aluminum and aluminum oxide, etc. Examples of the "particles containing copper" constituting the second nanopillar include particles made of copper, particles made of copper oxide, particles made of copper and copper oxide, etc.
[0020] (4) Still another aspect includes a case member having a first insertion hole and a second insertion hole, a first terminal member made of aluminum inserted into the first insertion hole of the case member, a second terminal member made of copper inserted into the second insertion hole of the case member, a first resin member inserted by insert molding that hermetically bonds the case member and the first terminal member while insulating them from each other and fixes the first terminal member to the case member, and a second resin member inserted by insert molding that hermetically bonds the case member and the second terminal member while insulating them from each other and fixes the second terminal member to the case member, wherein the first resin member has a resin linear expansion coefficient α of 1.6×10 -5 ~2.7×10 -5 Within the range of (1 / K) (1.6×10 -5 ≦α≦2.7×10 -5 and the second resin member is made of a second resin material different from the first resin material and having a resin bending modulus E of 17 GPa or less (E≦17), the method comprising: a first insert molding step of insert-molding the first resin member using the first resin material having the resin linear expansion coefficient α with the first terminal member being inserted into the first insertion hole of the case member; and a second insert molding step of insert-molding the second resin member using the second resin material having the resin bending modulus E with the second terminal member being inserted into the second insertion hole of the case member.
[0021] In the manufacturing method of the electric storage device described above, since the first resin member is insert-molded using the first resin material having the resin linear expansion coefficient α described above in the first insert molding step, cracks are unlikely to occur in the first resin member during molding, and the sealing performance between the first terminal member and the first resin member can be well maintained. Furthermore, since the second resin member is insert-molded using the second resin material having the resin bending elastic modulus E described above in the second insert molding step, cracks are unlikely to occur in the second resin member during molding, and the sealing performance between the second terminal member and the second resin member can be well maintained. Note that the first insert molding step and the second insert molding step may be performed separately or simultaneously.
[0022] (5) In the method for producing an electricity storage device according to (4), the second insert molding step may be carried out first, and then the first insert molding step may be carried out.
[0023] The first terminal member made of aluminum has a larger linear expansion coefficient than the second terminal member made of copper. Therefore, if the first insert molding step is performed first, cracks are likely to occur in the first resin member due to temperature changes in the subsequent second insert molding step. In contrast, in the manufacturing method for an electricity storage device described above, the second insert molding step is performed first, so the first resin member is not present in the second insert molding step, and therefore no cracks will occur in the first resin member.
[0024] (6) The method for producing an electricity storage device according to (4) or (5), wherein the first terminal member, a first terminal seal portion to which the first resin member is airtightly joined has a surface on which first nanopillars with a height of 50 nm or more are formed by aluminum-containing particles with a diameter of 100 nm or less linked in a string of beads to form a columnar shape, and the first resin member is airtightly joined to the first terminal seal portion by filling the spaces between the first nanopillars with the first resin material; the second terminal member, a second terminal seal portion to which the second resin member is airtightly joined has a surface on which second nanopillars with a height of 50 nm or more are formed by copper-containing particles with a diameter of 100 nm or less linked in a string of beads to form a columnar shape, and the second resin member is airtightly joined to the second terminal seal portion by filling the spaces between the second nanopillars with the second resin material; It is preferable that the method for manufacturing an electricity storage device further includes a first nanopillar formation step of irradiating the first terminal seal portion of the first terminal member with pulsed laser light while shifting the irradiation position prior to the insert molding step, to form the first nanopillars standing in a forest on the first terminal seal portion, and a second nanopillar formation step of irradiating the second terminal seal portion of the second terminal member with pulsed laser light while shifting the irradiation position prior to the second insert molding step, to form the second nanopillars standing in a forest on the second terminal seal portion, wherein the first insert molding step molds the first resin member while filling the spaces between the standing first nanopillars of the first terminal seal portion with the first resin material, and the second insert molding step molds the second resin member while filling the spaces between the standing second nanopillars of the second terminal seal portion with the second resin material.
[0025] In the above-mentioned method for manufacturing an electricity storage device, the first nanopillars are formed on the surface of the first terminal seal portion by irradiating laser light as described above in the first nanopillar formation step, so that the first nanopillars can be easily formed in the first terminal seal portion. Then, the first resin member is molded while filling the spaces between the first nanopillars with the first resin material in the first insert molding step, so that the bonding strength between the first terminal seal portion of the first terminal member and the first resin member can be increased, and the sealing property between the first terminal member and the first resin member can be maintained particularly well. Furthermore, since the second nanopillars are formed on the surface of the second terminal seal portion by irradiating the laser light as described above in the second nanopillar formation step, the second nanopillars can be easily formed in the second terminal seal portion. Then, since the second resin member is molded while filling the spaces between the second nanopillars with the second resin material in the second insert molding step, the bonding strength between the second terminal seal portion of the second terminal member and the second resin member can be increased, and the sealing property between the second terminal member and the second resin member can be maintained particularly well. [Brief description of the drawings]
[0026] [Figure 1] FIG. 1 is a perspective view of a battery according to an embodiment. [Diagram 2] 1 is a partially cutaway cross-sectional view of a battery according to an embodiment of the present invention taken along the battery height direction and the battery width direction. [Diagram 3] 1A and 1B are enlarged cross-sectional views of the vicinity of the positive electrode terminal member (negative electrode terminal member) and the first resin member (second resin member) of a battery according to an embodiment, where (a) is an enlarged cross-sectional view along the battery height direction and the battery width direction, and (b) is an enlarged cross-sectional view along the battery height direction and the battery thickness direction. [Figure 4] FIG. 2 is a partially enlarged cross-sectional view of the vicinity of the surface of a positive electrode terminal seal portion (negative electrode terminal seal portion, first lid seal portion, second lid seal portion) in a battery according to an embodiment. [Diagram 5] 3 is an explanatory diagram showing a cross section of a first resin material (second resin material) with regard to a method for measuring a resin linear expansion coefficient α and a resin bending elastic modulus E. FIG. [Figure 6] FIG. 2 is an explanatory diagram showing a method for measuring the flexural modulus E of a resin material. [Figure 7] 2 is a flowchart of a method for manufacturing a battery according to an embodiment. [Figure 8] FIG. 2 is an explanatory diagram showing a positive electrode nanopillar forming step (negative electrode nanopillar forming step, lid nanopillar forming step) in the battery manufacturing method according to the embodiment. [Figure 9] FIG. 11 is an explanatory diagram of the second insert molding process in the manufacturing method of the battery according to the embodiment, where (a) shows the negative electrode terminal member being inserted into the second insertion hole of the case lid member, and (b) shows the second resin member being molded. [Figure 10] FIG. 1 is an explanatory diagram of a first insert molding step in a manufacturing method for a battery according to an embodiment, where (a) shows the state in which a positive terminal member is inserted into a first insertion hole in a case lid member, and (b) shows the state in which a first resin member is molded. [Figure 11] 10 is a graph showing the relationship between the resin linear expansion coefficient α of the first resin material of the positive electrode and the length of a crack generated in the first resin member after a thermal cycle test. [Figure 12] 1 is a graph showing the relationship between the resin material flexural modulus E of the first resin material of the positive electrode and the length of a crack generated in the first resin member after a thermal cycle test. [Figure 13] 10 is a graph showing the relationship between the resin material flexural modulus E of the second resin material of the negative electrode and the length of a crack generated in the second resin member after a thermal cycle test. [Figure 14] 10 is a graph showing the relationship between the resin linear expansion coefficient α of the second resin material of the negative electrode and the length of a crack generated in the second resin member after a thermal cycle test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. FIG. 1 shows a perspective view of a battery (electricity storage device) 1 according to this embodiment, and FIG. 2 shows a partially cutaway cross-sectional view of the battery 1. FIG. 3 shows a partially enlarged cross-sectional view of the vicinity of the positive terminal member 50 (negative terminal member 60) and the first resin member 70 (second resin member 80). FIG. 4 shows a partially enlarged cross-sectional view of the vicinity of the surface 52m (surface 62m) of the positive terminal seal portion 52 (negative terminal seal portion 62). In the following, the battery height direction AH, the battery width direction BH, and the battery thickness direction CH of the battery 1 will be defined as the directions shown in FIG. 1 and FIG. 2 for description. The battery 1 is a rectangular (rectangular) sealed lithium ion secondary battery mounted on vehicles such as hybrid cars, plug-in hybrid cars, and electric cars.
[0028] The battery 1 is composed of a case 10, an electrode assembly 40 accommodated in the case 10, a positive electrode terminal member (first terminal member) 50 fixed to the case 10 via a first resin member 70, and a negative electrode terminal member (second terminal member) 60 fixed to the case 10 via a second resin member 80. The electrode assembly 40 is covered in a bag-shaped insulating holder 7 made of an insulating film inside the case 10. An electrolyte 5 is also accommodated inside the case 10, a part of which is impregnated in the electrode assembly 40, and the remainder is pooled on the bottom wall of the case 10.
[0029] The case 10 is a rectangular parallelepiped box made of metal (aluminum in this embodiment), and is configured from a case body member 20 having a rectangular opening 20c and a bottomed square cylinder shape that houses the electrode body 40 therein, and a rectangular plate-shaped case lid member 30 that closes the opening 20c of the case body member 20. In this embodiment, the case lid member 30 corresponds to the above-mentioned "case member." The opening 20c of the case body member 20 and the peripheral portion 30f of the case lid member 30 are hermetically welded around the entire circumference. Case lid member 30 of case 10 is provided with a safety valve 11 that breaks and opens when the internal pressure of case 10 exceeds a valve opening pressure. Case lid member 30 is also provided with a liquid injection hole 30k that penetrates case lid member 30, and this liquid injection hole 30k is airtightly sealed with a disk-shaped sealing member 12 made of aluminum.
[0030] The electrode assembly 40 housed in the case 10 is a rectangular parallelepiped laminated type, in which a plurality of positive electrode plates 41 and a plurality of negative electrode plates 42 are alternately laminated in the battery thickness direction CH with separators 43 made of porous resin films interposed between them. The positive electrode plates 41, the negative electrode plates 42, and the separators 43 each have a rectangular shape extending in the battery height direction AH and the battery width direction BH. The positive electrode plate 41 is composed of a positive electrode current collector foil made of aluminum foil and a positive electrode active material layer containing positive electrode active material particles formed on both main surfaces of the positive electrode current collector foil. A part of the positive electrode current collector foil extends to one side BH1 in the battery width direction BH, and the positive electrode active material layer is not present on both sides, forming a positive electrode foil exposed portion. The positive electrode foil exposed portions of each positive electrode plate 41 overlap in the foil thickness direction to form a positive electrode current collector 40c. The positive electrode current collector 40c is electrically connected to a positive electrode terminal member 50 described later.
[0031] The negative electrode plate 42 is composed of a negative electrode current collector foil made of copper foil and a negative electrode active material layer containing positive electrode active material particles formed on both main surfaces of the negative electrode current collector foil. A part of the negative electrode current collector foil extends to the other side BH2 in the battery width direction BH, and is an exposed negative electrode foil portion on both sides of the negative electrode current collector foil without the negative electrode active material layer. The negative electrode foil exposed portions of the negative electrode plates 42 overlap in the foil thickness direction to form a negative electrode current collector 40d. The negative electrode current collector 40d is conductively connected to a negative electrode terminal member 60 described later.
[0032] A rectangular first insertion hole 30h1 penetrating the case lid member 30 is provided near an end of one side BH1 in the battery width direction BH of the case lid member 30, and a rectangular second insertion hole 30h2 penetrating the case lid member 30 is provided near an end of the other side BH2 in the battery width direction BH of the case lid member 30. A positive electrode terminal member 50 made of aluminum is inserted into the first insertion hole 30h1, and the positive electrode terminal member 50 is fixed to the case lid member 30 in a state insulated from the case lid member 30 via the first resin member 70. A negative electrode terminal member 60 made of copper is inserted into the second insertion hole 30h2, and the negative electrode terminal member 60 is fixed to the case lid member 30 in a state insulated from the case lid member 30 via the second resin member 80.
[0033] First, the positive electrode will be described. The positive electrode terminal member 50 (see FIG. 3 in addition to FIG. 1 and FIG. 2) is made by pressing an aluminum plate, and is composed of a rectangular plate-shaped positive electrode terminal outer part 51 located outside the case lid member 30 (upper side AH1 in the battery height direction AH) and extending in the battery width direction BH and the battery thickness direction CH, a positive electrode terminal inner part 53 located inside the case lid member 30 (lower side AH2 in the battery height direction AH) and extending in the battery height direction AH, and a positive electrode terminal seal part (first terminal seal part) 52 connected to the positive electrode terminal outer part 51 and the positive electrode terminal inner part 53 via the first insertion hole 30h1. The positive electrode terminal seal part 52 is bent at an end part on one side CH1 of the positive electrode terminal outer part 51 in the battery thickness direction CH and extends to the lower side AH2, and penetrates a first resin member 70 described later in the battery height direction AH. Moreover, the positive terminal inside portion 53 is welded to the positive current collecting portion 40c of the electrode body 40 at the tip portion of the lower side AH2, and is electrically connected to the positive current collecting portion 40c.
[0034] The surface 51m of the positive terminal outer part 51 has a rectangular top surface 51ma facing the upper side AH1, a rectangular inner side surface 51mb facing the lower side AH2, and an end surface 51mc connecting these, and among these, the inner side surface 51mb and the end surface 51mc are joined to the first resin member 70. However, in this embodiment, positive electrode nanocolumns, which will be described later, are not formed on these inner side surface 51mb and end surface 51mc.
[0035] On the other hand, the first resin member 70 is airtightly joined to the positive electrode terminal seal part 52. Specifically, the surface 52m of the positive electrode terminal seal part 52 has a first main surface 52ma facing one side CH1 in the battery thickness direction CH, a second main surface 52mb facing the other side CH2 in the battery thickness direction CH, and a pair of end surfaces 52mc connecting them. As shown in FIG. 4, the surface 52m is forested with positive electrode nanopillars (first nanopillars) 55, each of which is made of aluminum and aluminum oxide particles 55p linked together in a string to form a columnar shape. The diameter Da of the particles 55p is 100 nm or less (in this embodiment, approximately Da=30 nm), and the height ha of the positive electrode nanopillars 55 is 50 nm or more (in this embodiment, approximately ha=200 nm). The first resin member 70 described below has a first resin material 75 filled between these adjacent positive electrode nanopillars 55, and is airtightly bonded to the positive electrode terminal seal portion 52.
[0036] In addition, the first resin member 70 is airtightly joined to the first lid seal portion 31 surrounding the first insertion hole 30h1 (see FIG. 3). Specifically, the first lid seal portion 31 has a rectangular annular outer surface 31m facing the outside (upper side AH1) and a rectangular annular inner surface 31n facing the inside (lower side AH2). On these surfaces, like the surface 52m of the positive electrode terminal seal portion 52 (see FIG. 4), there are forested first lid nanopillars 35, each of which is a columnar shape formed by bonding together particles 35p made of aluminum and aluminum oxide in a string-like manner. The diameter Da of the particles 35p is 100 nm or less (in this embodiment, Da is approximately 30 nm), and the height ha of the first lid nanopillars 35 is 50 nm or more (in this embodiment, ha is approximately 200 nm). A first resin member 70, which will be described later, is airtightly joined to the first lid seal portion 31 by filling the spaces between these standing first lid nanopillars 35 with a first resin material 75.
[0037] Next, the negative electrode will be described. The negative electrode terminal member 60 has the same shape as the positive electrode terminal member 50 (see Figs. 1 to 3). The negative electrode terminal member 60 is formed by pressing a copper plate, and is composed of a rectangular plate-shaped negative electrode terminal outer part 61 located on the outside (upper side AH1) of the case lid member 30 and extending in the battery width direction BH and the battery thickness direction CH, a negative electrode terminal inner part 63 located on the inside (lower side AH2) of the case lid member 30 and extending in the battery height direction AH, and a negative electrode terminal seal part (second terminal seal part) 62 connected to the negative electrode terminal outer part 61 and the negative electrode terminal inner part 63 via the second insertion hole 30h2. The negative electrode terminal seal part 62 is bent at an end part on one side CH1 of the negative electrode terminal outer part 61 in the battery thickness direction CH, extends to the lower side AH2, and penetrates a second resin member 80 described later in the battery height direction AH. Furthermore, the negative terminal inside portion 63 is welded to the negative current collector 40d of the electrode body 40 at the tip portion of the lower side AH2, and is conductively connected to the negative current collector 40d.
[0038] The surface 61m of the negative electrode terminal outer part 61 has a rectangular top surface 61ma facing the upper side AH1, a rectangular inner side surface 61mb facing the lower side AH2, and an end surface 61mc connecting these, and among these, the inner side surface 61mb and the end surface 61mc are joined to the second resin member 80. However, in this embodiment, negative electrode nano-columns described later are not formed on these inner side surface 61mb and end surface 61mc.
[0039] On the other hand, the second resin member 80 is airtightly joined to the negative electrode terminal seal part 62. Specifically, the surface 62m of the negative electrode terminal seal part 62 has a first main surface 62ma facing one side CH1 in the battery thickness direction CH, a second main surface 62mb facing the other side CH2 in the battery thickness direction CH, and a pair of end surfaces 62mc connecting them. On this surface 62m (see FIG. 4), negative electrode nanopillars (second nanopillars) 65, each of which is made of copper and copper oxide particles 65p linked together in a string-like shape, stand in a forest. The diameter Da of the particles 65p is 100 nm or less (in this embodiment, approximately Da=30 nm), and the height ha of the negative electrode nanopillars 65 is 50 nm or more (in this embodiment, approximately ha=200 nm). A second resin member 80 described later has a second resin material 85 filled between the adjacent negative electrode nanopillars 65 and is airtightly bonded to the negative electrode terminal seal portion 62 .
[0040] In addition, the second resin member 80 is airtightly joined to the second lid seal portion 32 of the case lid member 30 surrounding the second insertion hole 30h2 (see FIG. 3). Specifically, the second lid seal portion 32 has a rectangular annular outer surface 32m facing the outside (upper side AH1) and a rectangular annular inner surface 32n facing the inside (lower side AH2). On these surfaces, like the outer surface 32m and the inner surface 32n of the first lid seal portion 31 (see FIG. 4), second lid nanopillars 36 are arranged in a columnar shape formed by connecting particles 36p made of aluminum and aluminum oxide in a string-like manner. The diameter Da of the particles 36p is 100 nm or less (in this embodiment, approximately Da = 30 nm), and the height ha of the second lid nanopillars 36 is 50 nm or more (in this embodiment, approximately ha = 200 nm). A second resin member 80, which will be described later, is airtightly joined to the second lid seal portion 32 by filling the spaces between these standing second lid nanopillars 36 with a second resin material 85.
[0041] Next, the first resin member 70 of the positive electrode will be described (see Figs. 1 to 4). The first resin member 70 is joined to the case lid member 30 and the positive electrode terminal member 50 while insulating the case lid member 30 and the positive electrode terminal member 50, and fixes the positive electrode terminal member 50 to the case lid member 30. In detail, the first resin member 70 is airtightly joined to the positive electrode terminal seal portion 52 by filling the spaces between the adjacent positive electrode nano-pillars 55 of the positive electrode terminal seal portion 52 of the positive electrode terminal member 50 with a first resin material 75 described later. The first resin member 70 is airtightly joined to the first lid seal portion 31 by filling the spaces between the adjacent first lid nano-pillars 35 of the first lid seal portion 31 of the case lid member 30 with the first resin material 75.
[0042] The first resin member 70 is composed of a first resin outer portion 71 located on the outer side (upper side AH1) of the case lid member 30, and a first resin inner portion 72 located on the inner side (lower side AH2) of the case lid member 30 and within the first insertion hole 30h1 and connected to the first resin outer portion 71. The first resin member 70 has a resin linear expansion coefficient α of 1.6×10 in a temperature range of −40 to 65° C. -5 ~2.7×10 -5 (1 / K). In this embodiment, α=2.3×10 -5 (1 / K).
[0043] The first resin material 75 is composed of a thermoplastic first main resin 76, a thermoplastic first elastomer 77, and a first filler 78. Specifically, in this embodiment, the first main resin 76 is polyphenylene sulfide (PPS). The first elastomer 77 is a thermoplastic polyurethane elastomer (TPU) obtained from 4,4'-diphenylmethane diisocyanate (MDI) and polyester diol (PES). The first filler 78 is a fibrous (approximately 10 μm in diameter × 300 μm in length) glass filler made of alkali glass. The weight ratio of the first main resin 76, the first elastomer 77, and the first filler 78 is first main resin: first elastomer: first filler = 40: 10: 50.
[0044] Here, a method for measuring the resin linear expansion coefficient α of the first resin material 75 will be described (see FIG. 5). In this embodiment, since the first filler 78 contained in the first resin material 75 is fibrous, when the first filler 78 dispersed in the first resin material 75 is oriented, the resin linear expansion coefficient α of the first resin material 75 has a directional property. That is, when the first filler 78 is oriented in the direction in which the surface spreads, the first direction linear expansion coefficient αM in the first direction MD (in FIG. 5, the direction spreading in the left-right direction and the direction perpendicular to the paper surface) along the longitudinal direction of the first filler 78 and the second direction linear expansion coefficient αT in the second direction TD (in FIG. 5, the up-down direction) perpendicular to the first direction MD have different magnitudes. Therefore, the first direction linear expansion coefficient αM and the second direction linear expansion coefficient αT are obtained, respectively, and the average value is calculated to be the resin linear expansion coefficient α (α=(αM+αT) / 2).
[0045] Specifically, the linear expansion coefficient αM in the first direction and the linear expansion coefficient αT in the second direction of the first resin material 75 are obtained by digital image correlation (DIC). First, a rectangular parallelepiped test piece of the first resin material 75 in which the first filler 78 is oriented in the direction in which the surface spreads is prepared. The test piece is placed on a sample cooling and heating stage (for example, Japan High-Tech Co., Ltd.'s Large Sample Cooling and Heating Stage 10083L for Microscopes) so that the cross section along the first direction MD and the second direction (see FIG. 5) can be seen. Then, for the test piece in a state of 25° C., an initial image of the cross section of the test piece is obtained. The image is obtained using, for example, Keyence Corporation's Digital Microscope VHX-8000.
[0046] Then, the test piece is cooled to -40°C and then heated to 65°C, and images of the cross section of the test piece are obtained at each temperature of -40°C, 0°C, 25°C, 50°C, and 65°C. The obtained images are then analyzed using a DIC system (for example, GOM's DIC system ARAMIS), and an approximation line y=ax+b showing the relationship between temperature x and strain y in the first direction MD is obtained, and the slope a of this line is defined as the first direction linear expansion coefficient αM for the first direction MD. Also, an approximation line y=cx+d showing the relationship between temperature x and strain y in the second direction TD is obtained, and the slope c of this line is defined as the second direction linear expansion coefficient αT for the second direction TD. Furthermore, the average value of these is calculated ((αM+αT) / 2), and this is defined as the resin material linear expansion coefficient α.
[0047] Next, the second resin member 80 of the negative electrode will be described (see Figs. 1 to 4). The second resin member 80 is joined to the case lid member 30 and the negative terminal member 60 while insulating the case lid member 30 and the negative terminal member 60, and fixes the negative terminal member 60 to the case lid member 30. In detail, the second resin member 80 is airtightly joined to the negative terminal seal portion 62 by filling the spaces between the adjacent negative nano-pillars 65 of the negative terminal seal portion 62 of the negative terminal member 60 with a second resin material 85 described later. The second resin member 80 is airtightly joined to the second lid seal portion 32 by filling the spaces between the adjacent second lid nano-pillars 36 of the second lid seal portion 32 of the case lid member 30 with the second resin material 85.
[0048] The second resin member 80 has the same shape as the first resin member 70. The second resin member 80 is composed of a second resin outer portion 81 located on the outer side (upper side AH1) of the case lid member 30, and a second resin inner portion 82 located on the inner side (lower side AH2) of the case lid member 30 and in the second insertion hole 30h2 and connected to the second resin outer portion 81. The second resin member 80 is composed of a second resin material 85 different from the first resin material 75, and the resin material bending elasticity modulus E is 17 GPa or less. Furthermore, the resin material bending elasticity modulus E of the second resin material 85 is set to 10 GPa or more. Specifically, in this embodiment, E=16 GPa.
[0049] The second resin material 85 is composed of a thermoplastic second main resin 86, a thermoplastic second elastomer 87, and a second filler 88. In this embodiment, the second main resin 86, the second elastomer 87, and the second filler 88 are the same as the first main resin 76, the first elastomer 77, and the first filler 78 of the first resin material 75, respectively. However, the blending ratio of the second main resin 86, the second elastomer 87, and the second filler 88 in the second resin material 85 is different from the blending ratio of the first main resin 76, the first elastomer 77, and the first filler 78 in the first resin material 75. Specifically, the weight ratio of the second main resin 86, the second elastomer 87, and the second filler 88 is second main resin:second elastomer:second filler=40:15:45.
[0050] Here, a method for measuring the resin material bending elastic modulus E of the second resin material 85 will be described (see FIG. 6). In this embodiment, since the second filler 88 contained in the second resin material 85 is fibrous, when the second filler 88 dispersed in the second resin material 85 is oriented, the resin material bending elastic modulus E of the second resin material 85 has a directionality. That is, when the second filler 88 is oriented in the direction in which the surface spreads (see FIG. 5), the first direction bending elastic modulus EM in the first direction MD along the longitudinal direction of the second filler 88 and the second direction bending elastic modulus ET in the second direction TD perpendicular to the first direction MD have different magnitudes. Therefore, the first direction bending elastic modulus EM and the second direction bending elastic modulus ET are obtained, respectively, and the average value is calculated to be the resin material bending elastic modulus E (E=(EM+ET) / 2).
[0051] Specifically, the first direction bending elastic modulus EM and the second direction bending elastic modulus ET are obtained by performing a three-point bending test. First, two types of rectangular parallelepiped test pieces (length 10 mm x width 1.5 mm x thickness 1.5 mm) of the second resin material 85 in which the second filler 88 is oriented in the direction in which the surface spreads are prepared. In one test piece, the first direction MD coincides with the length direction (left-right direction in FIG. 6) and width direction (direction perpendicular to the paper surface in FIG. 6) of the test piece, and the second direction TD coincides with the thickness direction (up-down direction in FIG. 6) of the test piece. In the other test piece, the second direction TD coincides with the length direction of the test piece, and the first direction MD coincides with the width direction and thickness direction of the test piece.
[0052] Next, at an environmental temperature of 23°C, a test piece of the second resin material 85 is placed on a pair of supports SA with a fulcrum distance L of 8 mm, and the center of the length of the test piece is pressed downward with a force F of 1 kN by the pressing part SB. The radius R1 of the tip of the support part SA and the radius R2 of the tip of the pressing part SB are both 1.5 mm. For each test piece, the first direction bending elastic modulus EM and the second direction bending elastic modulus ET are obtained, and their average value is calculated ((EM+ET) / 2), which is defined as the bending elastic modulus E of the resin material.
[0053] In the battery 1 of this embodiment, as described above, the first resin member 70 and the second resin member 80 are formed from different resin materials. The first resin material 75 constituting the first resin member 70 has a resin linear expansion coefficient α of 1.6×10 -5 ~2.7×10 -5 (1 / K), and the second resin material 85 constituting the second resin member 80 has a resin material flexural modulus E of 17 GPa or less. Furthermore, the resin material flexural modulus E of the second resin material 85 is set to 10 GPa or more. As a result, as will be described later, cracks are less likely to occur in the first resin member 70 and the second resin member 80 during insert molding, and the sealing performance between the positive electrode terminal member 50 and the first resin member 70, and the sealing performance between the negative electrode terminal member 60 and the second resin member 80 can be well maintained.
[0054] Furthermore, in this embodiment, since the first resin material 75 is a resin material having a thermoplastic first elastomer 77 and a first filler 78 in addition to a thermoplastic first main resin 76, it is possible to easily adjust the magnitude of the resin linear expansion coefficient α of the first resin material 75. Furthermore, since the second resin material 85 is a resin material having a thermoplastic second elastomer 87 and a second filler 88 in addition to a thermoplastic second main resin 86, it is possible to easily adjust the magnitude of the resin bending elastic modulus E of the second resin material 85.
[0055] In this embodiment, the positive electrode nanopillars 55 described above stand in a forest on the surface 52m of the positive electrode terminal seal portion 52 of the positive electrode terminal member 50, and a first resin material 75 is filled between these positive electrode nanopillars 55, so that the first resin member 70 is airtightly joined to the positive electrode terminal seal portion 52. This increases the joining strength between the positive electrode terminal seal portion 52 of the positive electrode terminal member 50 and the first resin member 70, and makes it possible to maintain particularly good sealing performance between the positive electrode terminal member 50 and the first resin member 70. Furthermore, the above-mentioned negative electrode nanopillars 65 stand in a forest on the surface 62m of the negative electrode terminal seal portion 62 of the negative electrode terminal member 60, and the spaces between these negative electrode nanopillars 65 are filled with a second resin material 85, so that the second resin member 80 is airtightly bonded to the negative electrode terminal seal portion 62. This increases the bonding strength between the negative electrode terminal seal portion 62 of the negative electrode terminal member 60 and the second resin member 80, and makes it possible to maintain particularly good sealing performance between the negative electrode terminal member 60 and the second resin member 80.
[0056] Next, a manufacturing method of the battery 1 will be described (see Figs. 7 to 10). First, a case lid member (case member) 30Z before roughening is prepared. The case lid member 30Z before roughening is obtained by punching an aluminum plate into a predetermined shape and forming a liquid injection hole 30k, a first insertion hole 30h1, a second insertion hole 30h2, and a safety valve 11 therein. A positive electrode terminal member (first terminal member) 50Z before roughening is also prepared. The positive electrode terminal member 50Z before roughening is obtained by punching an aluminum plate into a predetermined shape and bending the plate. A negative electrode terminal member (second terminal member) 60Z before roughening is also prepared. The negative electrode terminal member 60Z before roughening is obtained by punching a copper plate into a predetermined shape and bending the plate.
[0057] Then, in the "positive electrode nanopillar formation process (first nanopillar formation process) S1" (see FIG. 7), the positive electrode terminal seal portion 52 of the positive electrode terminal member 50Z is irradiated with pulsed laser light LC while shifting the irradiation position (see FIG. 8), to form a forest of positive electrode nanopillars 55 on the surface 52m of the positive electrode terminal seal portion 52. As described above (also see FIG. 4), the positive electrode nanopillars 55 are formed by particles 55p made of aluminum and aluminum oxide linked together in a string-like pattern to form a columnar shape.
[0058] In this embodiment, the laser irradiation conditions are as follows: wavelength 1064 nm, peak output 5 kW, pulse width 150 ns, pitch pb 75 μm, and spot diameter Db 80 μm. In the circular area of the positive terminal seal portion 52 irradiated with the laser light LC in plan view, aluminum near the surface 52 m melts and becomes aluminum vapor. When the temperature of the vapor is then reduced, the aluminum and aluminum oxide particles 55 p are formed and deposited on the surface 52 m of the positive terminal seal portion 52. By irradiating the positive terminal seal portion 52 with the laser light LC while shifting the irradiation position, the particles 55 p are deposited in a string of beads and bonded to form columns, forming a forest of positive nano-columns 55.
[0059] Separately, in the "negative electrode nanopillar formation process (second nanopillar formation process) S2" (see FIG. 7), the negative electrode terminal seal portion 62 of the negative electrode terminal member 60Z is irradiated with pulsed laser light LC while shifting the irradiation position (see FIG. 8), to form a forest of negative electrode nanopillars 65 on the surface 62m of the negative electrode terminal seal portion 62. As described above (also see FIG. 4), the negative electrode nanopillars 65 are formed by particles 65p made of copper and copper oxide linked together in a string-like pattern to form a columnar shape.
[0060] In this embodiment, the laser irradiation conditions are as follows: wavelength 1064 nm, peak output 20 kW, pulse width 50 ns, pitch pb 60 μm, and spot diameter Db 75 μm. In the area of the negative terminal seal part 62 that is circular in plan view and irradiated with the laser light LC, the copper near the surface 62 m melts and becomes copper vapor. When the temperature of the vapor is then reduced, the copper and copper oxide particles 65 p are formed and deposited on the surface 62 m of the negative terminal seal part 62. By irradiating the negative terminal seal part 62 with the laser light LC while shifting the irradiation position, the particles 65 p are deposited in a string of beads and bonded to form columns, forming a forest of negative nano-columns 65.
[0061] Separately, in the "lid nanopillar formation step S3" (see FIG. 7), the first lid seal portion 31 of the case lid member 30Z is irradiated with pulsed laser light LC while shifting the irradiation position (see FIG. 8), to form first lid nanopillars 35 standing in a forest on the outer side surface 31m and inner side surface 31n of the first lid seal portion 31. The second lid seal portion 32 of the case lid member 30Z is also irradiated with pulsed laser light LC while shifting the irradiation position, to form second lid nanopillars 36 standing in a forest on the outer side surface 32m and inner side surface 32n of the second lid seal portion 32. As described above (see also FIG. 4), the first lid nanopillars 35 and the second lid nanopillars 36 are formed by particles 35p, 36p made of aluminum and aluminum oxide being linked together in a string of beads to form a columnar shape. In this embodiment, the laser irradiation conditions are the same as those in the positive electrode nanopillar formation step S1.
[0062] Next, in the "second insert molding process S4" (see FIG. 7), with the negative terminal member 60 inserted into the second insertion hole 30h2 of the case cover member 30, the second resin member 80 is insert molded using a second resin material 85 having a resin material bending elastic modulus E within the aforementioned range (see FIG. 9). Specifically, the second insert molding step S4 is performed using a molding die (not shown) having an upper die and a lower die. First, the case lid member 30 is placed at a predetermined position in the lower die, and the negative terminal member 60 is inserted into the second insertion hole 30h2 of the case lid member 30 (see FIG. 9(a)). After that, the upper die is moved toward the lower die to close the molding die. Next, the molten second resin material 85 is injected into the cavity of the molding die. At that time, the second resin material 85 is filled between the adjacent negative nano-pillars 65 of the negative terminal seal portion 62 and between the adjacent second lid nano-pillars 36 of the second lid seal portion 32, and the second resin member 80 that is airtightly joined to the negative terminal seal portion 62 and the second lid seal portion 32 is molded (see FIG. 9(b)). After that, the lid assembly 15 in which the negative terminal member 60 is fixed to the case lid member 30 via the second resin member 80 is taken out of the molding die.
[0063] Next, in the "first insert molding process S5" (see FIG. 7), with the positive terminal member 50 inserted into the first insertion hole 30h1 of the case lid member 30 of the above-mentioned lid assembly 15, the first resin member 70 is insert molded using a first resin material 75 having a resin linear expansion coefficient α within the aforementioned range (see FIG. 10). Specifically, a molding die (not shown) having an upper die and a lower die is used. First, the lid assembly 15 is placed at a predetermined position in the lower die, and the positive electrode terminal member 50 is inserted into the first insertion hole 30h1 of the case lid member 30 (see FIG. 10(a)). After that, the upper die is moved toward the lower die to close the molding die. Next, the molten first resin material 75 is injected into the cavity of the molding die. At that time, the first resin material 75 is filled between the adjacent positive electrode nano-pillars 55 of the positive electrode terminal seal portion 52 and between the adjacent first lid nano-pillars 35 of the first lid seal portion 31, and the first resin member 70 that is airtightly joined to the positive electrode terminal seal portion 52 and the first lid seal portion 31 is molded (see FIG. 10(b)). Thereafter, this lid assembly 16 (the lid assembly 16 in which the positive electrode terminal member 50 is fixed to the case lid member 30 via the first resin member 70 and the negative electrode terminal member 60 is fixed to the case lid member 30 via the second resin member 80) is removed from the molding die.
[0064] Next, in the "electrode body connecting step S6" (see FIG. 7), an electrode body 40 is prepared by stacking a positive electrode plate 41, a negative electrode plate 42, and a separator 43, and the positive electrode terminal inner portion 53 of the positive electrode terminal member 50 of the lid assembly 16 described above is welded to the positive electrode current collecting portion 40c of the electrode body 40. Also, the negative electrode terminal inner portion 63 of the negative electrode terminal member 60 of the lid assembly 16 is welded to the negative electrode current collecting portion 40d of the electrode body 40. Thereafter, the electrode body 40 is wrapped in a bag-shaped insulating holder 7. Next, in the "electrode assembly accommodating / case forming process S7", a case body member 20 is prepared, the electrode assembly 40 covered with the insulating holder 7 described above is inserted into the case body member 20, and the opening 20c of the case body member 20 is closed with the case lid member 30. Then, the opening 20c of the case body member 20 and the peripheral portion 30f of the case lid member 30 are laser-welded airtightly all around to form a case 10 accommodating the electrode assembly 40 therein.
[0065] Next, in a "pouring and sealing step S8", electrolyte 5 is poured into case 10 through pouring hole 30k, and electrolyte 5 is impregnated into electrode body 40. Thereafter, pouring hole 30k is covered from the outside with sealing member 12, and sealing member 12 is laser-welded to case 10 airtightly. Next, in the "initial charging and aging step S9", a charging device (not shown) is connected to the battery 1 to perform an initial charge on the battery 1. After that, the initially charged battery 1 is left to stand for a predetermined time to age the battery 1. In this way, the battery 1 is completed.
[0066] (Test Results) Next, the results of tests carried out to verify the effects of the present invention will be described (see Figs. 11 to 14). First, a first resin member 70 of the positive electrode was insert-molded using a plurality of first resin materials 75 with different resin linear expansion coefficients α. Specifically, for each of the first resin materials 75, only the positive electrode nano-pillar forming step S1, the lid nano-pillar forming step S3, and the first insert molding step S5 were carried out, and a lid assembly in which only the positive electrode terminal member 50 was fixed to the case lid member 30 via the first resin member 70 was obtained.
[0067] Then, these lid assemblies were subjected to a thermal cycle test in the temperature range of -40°C to 65°C, taking into consideration the temperature conditions of the battery. Specifically, using a liquid tank tester, the lid assembly was immersed in a liquid tank at -40°C for 3 minutes, and then immersed in a liquid tank at 65°C for 3 minutes, with this cycle being one cooling / heating cycle, and this was performed 3650 times. Then, for each lid assembly, the length of the cracks occurring in the first resin member 70 near the boundary with the positive terminal member 50 was measured. The results are shown in FIG. 11. Note that the first resin member 70 in which no cracks occurred is shown as having a crack length of 0.0 mm. The same applies to the crack lengths in FIGS. 12 to 14 described later.
[0068] As is clear from the graph in FIG. 11, the resin linear expansion coefficient α is 1.5×10 -5 (1 / K) or less or 2.8×10 -5When the first resin member 70 is molded using the first resin material 75 having a linear expansion coefficient α of 1.6×10 -5 ~2.7×10 -5 When the first resin member 70 is molded using the first resin material 75 within the range of (1 / K) and subjected to a thermal cycle test, no cracks are generated in the first resin member 70. From this, it is considered that the resin linear expansion coefficient α of the first resin material 75 for the positive electrode is set to 1.6×10 -5 ~2.7×10 -5 It is found that it is best to keep it within the range of (1 / K).
[0069] Next, first resin members 70 were insert-molded using a plurality of first resin materials 75 with different resin material flexural modulus E values. Thereafter, a thermal cycle test was performed as described above, and the length of each crack generated in the first resin member 70 was measured. The results are shown in FIG. 12. Although details are omitted, the resin material linear expansion coefficient α of the first resin material 75 of each sample shown in FIG. 12 was within the aforementioned range (1.6×10 -5 ~2.7×10 -5 (1 / K)). 12, the magnitude of the resin material flexural modulus E of the first resin material 75 does not have much effect on the presence or absence of cracks, and it is found that cracks occur in the first resin member 70 even if the magnitude of the resin material flexural modulus E is changed. Therefore, in order to prevent cracks from occurring in the first resin member 70, it is necessary to set the resin material linear expansion coefficient α of the first resin material 75 to 1.6×10 as described above. -5 ~2.7×10 -5 It is best to keep it within the range of (1 / K).
[0070] Next, a second resin member 80 of the negative electrode was insert-molded using a plurality of second resin materials 85 in which the magnitude of the resin material bending elastic modulus E was changed. Specifically, for each second resin material 85, only the above-mentioned negative electrode nano-pillar forming step S2, the lid nano-pillar forming step S3, and the second insert molding step S4 were performed, and a lid assembly 15 (see FIG. 9(b)) in which only the negative electrode terminal member 60 was fixed to the case lid member 30 via the second resin member 80 was obtained. After that, the above-mentioned thermal cycle test was performed on these lid assemblies 15, and the length of the cracks occurring in the second resin member 80 near the boundary with the negative electrode terminal member 60 was measured. The results are summarized in FIG. 13.
[0071] 13, when the second resin member 80 is molded using a second resin material 85 having a resin material flexural modulus E of 19 GPa or more and a thermal cycle test is performed, cracks occur in the second resin member 80. In contrast, when the second resin member 80 is molded using a second resin material 85 having a resin material flexural modulus E of 17 GPa or less and a thermal cycle test is performed, no cracks occur in the second resin member 80. From this, it is found that for the negative electrode, it is preferable to set the resin material flexural modulus E of the second resin material 85 to 17 GPa or less.
[0072] Next, second resin members 80 were insert molded using a plurality of second resin materials 85 with different resin linear expansion coefficients α. The aforementioned thermal cycle test was then performed to measure the length of each crack that had occurred in the second resin member 80. The results are shown in FIG. 14. Although details are omitted, the resin flexural modulus E of the second resin material 85 of each sample shown in FIG. 14 is outside the aforementioned range (17 GPa or less). 14, it is understood that the magnitude of the resin linear expansion coefficient α of the second resin material 85 does not significantly affect the presence or absence of cracks. Therefore, in order to prevent cracks from occurring in the second resin member 80, it is preferable to set the resin flexural modulus E of the second resin material 85 to 17 GPa or less, as described above.
[0073] As described above, in the manufacturing method of the battery 1, in the first insert molding step S5, the first resin member 70 is insert molded using the first resin material 75 having the resin linear expansion coefficient α within the above-mentioned range, so that cracks are unlikely to occur in the first resin member 70 during molding, and the sealing performance between the positive electrode terminal member 50 and the first resin member 70 can be well maintained. In addition, in the second insert molding step S4, the second resin member 80 is insert molded using the second resin material 85 having the resin bending elastic modulus E within the above-mentioned range, so that cracks are unlikely to occur in the second resin member 80 during molding, and the sealing performance between the negative electrode terminal member 60 and the second resin member 80 can be well maintained.
[0074] The positive electrode terminal member 50 made of aluminum has a larger linear expansion coefficient than the negative electrode terminal member 60 made of copper. Therefore, if the first insert molding step S5 is performed first, cracks are likely to occur in the first resin member 70 due to temperature changes in the subsequent second insert molding step S4. In contrast, in this embodiment, since the second insert molding step S4 is performed first, the first resin member 70 is not present in the second insert molding step S4 (see FIG. 9), and therefore no cracks occur in the first resin member 70.
[0075] In this embodiment, the positive electrode nanopillars 55 are formed on the surface 52m of the positive electrode terminal seal portion 52 by irradiating the laser beam LC as described above in the positive electrode nanopillar formation step S1, so that the positive electrode nanopillars 55 can be easily formed in the positive electrode terminal seal portion 52. Then, in the first insert molding step S5, the first resin member 70 is molded while filling the spaces between the positive electrode nanopillars 55 with the first resin material 75, so that the bonding strength between the positive electrode terminal seal portion 52 of the positive electrode terminal member 50 and the first resin member 70 can be increased and the sealing property between the positive electrode terminal member 50 and the first resin member 70 can be maintained particularly well. Furthermore, in the negative electrode nanopillar formation step S2, the negative electrode nanopillars 65 are formed on the surface 62m of the negative electrode terminal seal portion 62 by irradiating the laser beam LC as described above, so that the negative electrode nanopillars 65 can be easily formed in the negative electrode terminal seal portion 62. Then, in the second insert molding step S4, the second resin member 80 is molded while filling the spaces between the negative electrode nanopillars 65 with the second resin material 85, so that the bonding strength between the negative electrode terminal seal portion 62 of the negative electrode terminal member 60 and the second resin member 80 can be increased and the sealing performance between the negative electrode terminal member 60 and the second resin member 80 can be maintained particularly well.
[0076] Although the present invention has been described above with reference to an embodiment, it goes without saying that the present invention is not limited to the embodiment and can be modified as appropriate without departing from the spirit of the present invention. [Explanation of symbols]
[0077] 1. Battery (energy storage device) 10 Cases 30 Case cover member (case member) 30h1 First insertion hole 30h2 Second insertion hole 40 Electrode body 50 Positive electrode terminal member (first terminal member) 52 Positive electrode terminal seal part (first terminal seal part) 52m (Positive terminal seal part) surface 55 Positive electrode nanopillar (first nanopillar) 55p particles 60 Negative electrode terminal member (second terminal member) 62 Negative terminal seal part (second terminal seal part) 62m (Positive terminal seal part) surface 65 Negative electrode nano pillar (second nano pillar) 65p particles 70 First resin member 75 First resin material 76 First main resin 77 First Elastomer 78 First Filler 80 Second resin member 85 Second resin material 86 Second Main Resin 87 Second Elastomer 88 Second Filler α Resin material linear expansion coefficient E Resin material flexural modulus LC Laser Light S1 Positive electrode nano pillar formation process (first nano pillar formation process) S2 Negative electrode nano pillar formation process (second nano pillar formation process) S4 Second insert molding process S5 1st insert molding process
Claims
1. a case member having a first insertion hole and a second insertion hole; a first terminal member made of aluminum and inserted into the first insertion hole of the case member; a second terminal member made of copper and inserted into the second insertion hole of the case member; a first resin member that is insert-molded to hermetically join the case member and the first terminal member while insulating them from each other and fixing the first terminal member to the case member; a second resin member formed by insert molding, hermetically joining the case member and the second terminal member while insulating them from each other and fixing the second terminal member to the case member. An electricity storage device, The first resin member is Resin linear expansion coefficient α is 1.6×10 -5 ~2.7 x 10 -5 Within the range of (1 / K) (1.6 x 10 -5 ≦α≦2.7×10 -5 ) a first resin material, The second resin member is The second resin material has a flexural modulus E of 17 GPa or less (E≦17), and is different from the first resin material. Energy storage device.
2. The power storage device according to claim 1 , The first resin material is a first thermoplastic main resin, a first thermoplastic elastomer, and a first filler; The second resin material is The composite material includes a second thermoplastic main resin, a second thermoplastic elastomer, and a second filler. Energy storage device.
3. The electricity storage device according to claim 1 or 2, The first terminal member has a first terminal seal portion to which the first resin member is hermetically joined, On the surface of the substrate, first nanopillars having a height of 50 nm or more are formed by connecting aluminum-containing particles having a diameter of 100 nm or less in a string-like shape, The first resin member is the first resin material is filled between the first nanopillars standing in a forest and is airtightly bonded to the first terminal seal portion, The second terminal member has a second terminal seal portion to which the second resin member is hermetically joined. On the surface of the nanoparticles, second nanoparticles having a height of 50 nm or more are formed by connecting copper-containing particles having a diameter of 100 nm or less in a string-like shape, The second resin member is The second resin material is filled between the adjacent second nano-pillars and is hermetically bonded to the second terminal seal portion. Energy storage device.
4. a case member having a first insertion hole and a second insertion hole; a first terminal member made of aluminum and inserted into the first insertion hole of the case member; a second terminal member made of copper and inserted into the second insertion hole of the case member; a first resin member that is insert-molded to hermetically join the case member and the first terminal member while insulating them from each other and fixing the first terminal member to the case member; a second resin member formed by insert molding, the second resin member being hermetically joined to the case member and the second terminal member while insulating them from each other, and fixing the second terminal member to the case member; The first resin member has a resin linear expansion coefficient α of 1.6×10 -5 ~2.7 x 10 -5 Within the range of (1 / K) (1.6 x 10 -5 ≦α≦2.7×10 -5 ) a first resin material, The second resin member is made of a second resin material different from the first resin material, the second resin material having a resin material flexural modulus E of 17 GPa or less (E≦17). A method for manufacturing an electricity storage device, comprising: a first insert molding step of insert-molding the first resin member using the first resin material having the resin linear expansion coefficient α in a state in which the first terminal member is inserted into the first insertion hole of the case member; a second insert molding step of insert-molding the second resin member using the second resin material having the resin material bending elastic modulus E in a state in which the second terminal member is inserted into the second insertion hole of the case member. A method for manufacturing an electricity storage device.
5. A method for producing the electricity storage device according to claim 4, comprising the steps of: The second insert molding step is carried out first, and then the first insert molding step is carried out. A method for manufacturing an electricity storage device.
6. A method for producing the electricity storage device according to claim 4 or 5, comprising the steps of: a first terminal seal portion to which the first resin member is hermetically bonded of the first terminal member has a surface on which first nanopillars having a height of 50 nm or more stand in a row, the first nanopillars being formed by aluminum-containing particles having a diameter of 100 nm or less and linked together in a string-like pattern; the first resin member is configured such that the first resin material is filled between the first nanopillars standing in a forest and is airtightly bonded to the first terminal seal portion, a second terminal seal portion to which the second resin member is hermetically bonded of the second terminal member has a surface on which second nanopillars having a height of 50 nm or more stand in a row, the second nanopillars being formed by connecting copper-containing particles having a diameter of 100 nm or less in a string-like manner; the second resin member is configured such that the second resin material is filled between the adjacent ones of the second nano-pillars standing in a forest and is airtightly bonded to the second terminal seal portion, a first nanopillar forming step of irradiating the first terminal seal portion of the first terminal member with a pulsed laser beam while shifting an irradiation position thereof, prior to the first insert molding step, to form the first nanopillars standing in a forest on the first terminal seal portion; a second nanopillar forming step of irradiating the second terminal seal portion of the second terminal member with a pulsed laser beam while shifting an irradiation position thereof, prior to the second insert molding step, to form a forest of the second nanopillars on the second terminal seal portion, The first insert molding step includes: molding the first resin member while filling spaces between the first nano-pillars standing in the first terminal seal portion with the first resin material; The second insert molding step includes: The second resin member is molded while filling the spaces between the second nano-pillars standing in the second terminal seal portion with the second resin material. A method for manufacturing an electricity storage device.
Citation Information
Patent Citations
Sealing plate for battery container, method for manufacturing it, and nonaqueous electrolyte cell
JP2008027823A
Insert resin molding product and method for manufacturing the same
JP2010052365A
Battery and battery manufacturing method
JP2022079172A